The Influence of E-Service Quality on Continuance Intention with Customer Satisfaction as an Intervening Variable on LinkAja Application Users in Bandung City - Ratu Edo, Jimmy Julio; Hendayani, Ratih (International Journal of Business, Management and Economics, 2023)
The development of electronic money in Indonesia has made many people start to switch to digital payment modes as an easy solution for conducting various non-cash transactions. The city of Bandung, one of the most densely populated cities in Indonesia, is the city with the most digital payment users. One of the digital payment applications used is LinkAja. This research was conducted to determine the factors that influence the intention to continue the use of the LinkAja application in the city of Bandung. These factors include e-service quality, customer satisfaction, perceived trust, perceived risk. convenience, social value, attitude, and effort expectancy. This study used a quantitative method through data collection by distributing questionnaires online to people who live in the city of Bandung as many as 260 respondents. Data analysis techniques using Structural Equation Modeling (SEM), that is Partial Least Square (PLS) with SmartPLS v.3.2.9 software. Based on the analysis that has been done, the findings in this study indicate that perceived trust, convenience, and social value have a significant positive effect on customer satisfaction. Then, customer satisfaction has a significant positive effect on attitude. Besides that, e-service quality significant positive effect on perceived trust, customer satisfaction, continuance intention, attitude, and effort expectancy LinkAja application users in the city of Bandung. Meanwhile, Attitude also has a significant positive effect on continuance intention, the perceived risk has no significant negative effect on continuance intention. However, effort expectancy has no significant positive effect on continuance intention directly to LinkAja application users in the city of Bandung. This study recommends that LinkAja application service providers must maintain its service quality and create competitive advantages in service quality, so that the number of customer satisfaction and continuance intention to continue the use of the LinkAja application in the city of Bandung increase.